Efektifitas Bimbingan Klasikal Dengan Materi Choice Theory Untuk Meningkatkan Kesiapan Karir Siswa Disabilitas Intelektual - Dzil 'Arifah Hasni; Masril Masril; Wahidah Fitriani; Yuliana Nelisma (Jurnal Counseling Care, 2022)
Classical guidance with choice theory material is effective in increasing the career readiness of students with intellectual disabilities at SLBN 1 Pagaruyung. The purpose of this study was to analyze the effectiveness of classical guidance with choice theory material to improve the career readiness of students with intellectual disabilities at SLBN 1 Pagaruyung. This type of research is quantitative research using experimental methods. The design used in this study is a pre-experimental design with the type of one group pre-test-post-test design by measuring the career readiness of students with intellectual disabilities at SLBN 1 Pagaruyung using the same instrument in the pre-test and post-test measurements. The population used as a sample in this study were students with intellectual disabilities in the SMALB education unit at SLBN 1 Pagaruyung, totaling 5 (five) students. The technique used is purposive sampling. The results showed that classical guidance with choice theory material was effective in increasing the career readiness of students with intellectual disabilities at SLBN 1 Pagaruyung. This can be proven by 1) an increase in career readiness in life skills, 2) an increase in career readiness in social skills, 3) an increase in career readiness in growing career habits, and 4) an increase in career readiness in skills to recognize possible jobs. Based on the results of the T-test analysis obtained thit (t0) of 6.47 and ttable (tt) of 2.015, it can be analyzed that t0 is greater than tt so Ha is accepted and H0 is rejected, this is interpreted by the statement that classical guidance with choice material theory is effective to improve the career readiness of students with intellectual disabilities at SLBN 1 Pagaruyung. The researcher recommends schools to be able to apply classical guidance with choice theory material as an effort to improve the career readiness of students with intellectual disabilities at SLBN 1 Pagaruyung.